Sistem Informasi Geografis Pariwisata Dengan Integerasi Global Positioning System dan Algoritma Dijkstra - Ahmad Mubarok; Supriyadi Supriyadi; Arif Budimansyah Purba (Jurnal ICT : Information Communication & Technology, 2019)
Geographic information system is a geospatial information system development of diverse data sources and heterogeneous includes news, events, routes and tourist attractions. The system provides information about the geographic location with integrated global positioning system (GPS). GPS is a system to determine the location on the earth's surface with the aid of the alignment of the satellite signal. GPS coordinates deci-sive point will be more complete if coupled with the use dijkstra algorithm to determine the shortest path to get to the tourist sites. Many tourist sites and have a short distance away from tourist spots and the other one is a problem because these sights are not known by the tourists who recently visited. In a case like this is necessary to travel guides which can provide information about the location - nearby tourist sites and pathways that can be bypassed by tourists. A cross between GPS and dijktra algorithms can be developed into a geographic information system based on Android that is interesting and informative in the field of tourism as a guide for tourists.